Cannibal capitalism how big business and the feds are ruining America - Hill, Michael, 1971- (Wiley, 2011)
"People, regular people, many of whom have never shown a previous interest in economics are now eager to understand this economy. The country is now facing the biggest economic collapse since the Great Depression. It affects everyone, not merely investors, bankers, economists, and the rest of the business class. People who have lived their lives by the rules and who are usually unaffected by recessions have been hurt and they want to know why. Many are hot mad that the government must intervene in behalf of those they perceive as crooks who swindled the nation, and yet they are afraid that their home will continue to erode in value, their retirement fund will be further emaciated, and their job may be lost. Angry, afraid, and confused, regular people are looking for answers. The book takes a thoughtful look at how income and wealth disparity, industry consolidation, anticompetitive business practices, political ideological extremism, and the hoarding of existing wealth are destroying the wealth building capacity of the nation, the promise of ideal capitalism"--